KEMAMPUAN SISWA KELAS IV SD INPRES SIKUMANA 2 KOTA KUPANG DALAM MEMBACA PEMAHAMAN CERITA DONGENG MELALUI PENGGUNAAN MEDIA KOMIK - Karus Margaritha; Agnes Debora Banamtuan; Andriyani A. D. Lehan (Journal of Character and ELementary Education, 2023)
This study aims to describe the Ability of Grade IV Students of SD Inpres Sikumana 2 Kota Kupang in Reading Comprehension of Fairy Tales through the Use of Comic Media. Data collection techniques used are interviews and tests. The subjects of this study were 28 grade IV students of SD Inpres Sikumana, 13 boys and 15 girls. The data analysis technique is descriptive qualitative. Based on the results of analysis of research data on the ability to read comprehension of fairy tales for fourth graders of SD Inpres Sikumana 2 Kupang City, of the 28 students studied, there were 6 students with 21.42% who were included in the good category in reading comprehension based on character, character traits, and core story, there are 7 students with a percentage of 25% who are in the sufficient category in reading comprehension of fairy tales based on characters, character traits, and the core of the story there are 9 students with a percentage of 32.14% and there are 6 students who are included in the category lacking in reading comprehension of fairy tales based on characters, character traits, and the core of the story with a percentage of 21.42%. Based on the presentation of the value obtained, it can be concluded that the average score obtained by the class is 81. This shows that the level of ability of class IV C students in reading comprehension of fairy tales based on characters, character traits, and the core of the story has reached an average KKM of 75.